The Interregional Partnership Model as an Attempt to Improve the Prosperity of Civil Society in East Java, Indonesia - ., Nasikh (KnE Social Sciences, 2018)
Interregional partnership is considered to be a medium to strengthen the relationship between regencies or cities within the country. This research is aiming at identifying the interregional partnership model in regencies or cities as an attempt to improve the prosperity of civil society in East Java. This research were conducted in five regencies in East Java, namely Lamongan, Tuban, Tulungagung, Kediri, and Madiun regencies. The finding of the research shows the interregional partnership model among regencies or cities as an attempt to improve the prosperity of civil society in East Java was carried out by applying the equal partnership, synergic, mutualism symbiosis, as well as need-based, involvement and ownership, flexibility, legitimate, effective, accountable and transparent, and sustainable principles. The East Java government has been playing an active and adequate role, even they have given the right proportion institutionally and substantially based on the constitution. There are some factors underlying the interregional partnership among regencies, which are transparency, robustness, transformation rules, government capacity, distributions of power, dependency level, and intellectual order. Keywords: partnership, interregional, local government